An Analysis Of Students’ Errors In Writing Procedure Text At Second Year Students Of SMK Cendana Padang Panjang - Erlinda Syam (FKIP UMSB, 2025)
This research has several purposes. The first was to find out the student errors in writing Procedure text at second year students of SMAN 2 Sungai Limau The research was conducted at This research was conducted at SMK CENDANA Padangpanjang, in Jl. H.Agus no.1, Guguk Malintang, Sumatera Barat,which involved 12 students of the 2 nd grade. This study collected data through writing testto generate qualitative information. The data was analyzed using percentages andfrequencies to obtain data results. The results showed that the students made errors in several types based onSurface Strategy Taxonomy: omission, addition, misformation, and misordering withtotal errors were 39 errors. omission is the most prevalent error, comprising 61.53% or 24errors of the total errors, indicating frequent neglect of important elements. Additionerrors follow at 28.20% or 11 errors, where irrelevant or unnecessary information disruptsthe clarity of instructions. Misformation errors account for 7.69% or 3 errors, affectingthe accuracy and comprehension of the text due to incorrect word usage. Misorderingerrors constitute only 2.05% or 1 error, but they can still impact the effectiveness of theprocedure if steps are not correctly sequenced. Questionaires suggested that